1997
DOI: 10.1063/1.118769
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial hardness enhancement in deuterium annealed 0.25 μm channel metal oxide semiconductor transistors

Abstract: Interfacial degradation induced by hot-electron injection has been studied in n-channel metal oxide semiconductor transistors with channel lengths down to 0.2 μm. The devices were annealed in either H2 or D2 containing atmospheres. The channel transconductance and threshold voltage variations induced by hot-electron injection into the gate are consistent with interface state generation. Charge pumping experiments confirm this conclusion. The lifetime for a 10% reduction in the transconductance is enhanced by ∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 6 publications
6
31
0
Order By: Relevance
“…From hydrogen-deuterium isotope experiments [1], it has recently been shown that hot electron degradation in MOSFETs is due in large part to the de-passivation of Si-H(D) bonds at the SiSiO 2 interface. These results have been verified by both academic [2] and corporate research [3] teams. The degradation in MOSFETs has been argued to be limited by hydrogen diffusion away from the interface into bulk SiO 2 .…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…From hydrogen-deuterium isotope experiments [1], it has recently been shown that hot electron degradation in MOSFETs is due in large part to the de-passivation of Si-H(D) bonds at the SiSiO 2 interface. These results have been verified by both academic [2] and corporate research [3] teams. The degradation in MOSFETs has been argued to be limited by hydrogen diffusion away from the interface into bulk SiO 2 .…”
Section: Introductionsupporting
confidence: 75%
“…The isotope effect [1][2][3] indicates that hydrogen plays a significant role in hot electron degradation of MOSFETs. With charge pumping measurements in 0.25 micron MOSFETs [2], the density of interface traps has been determined as a function of silicon Fermi energy position and hot electron stress. After hot electron stress, a distributions emerged with two peaks at 0.25 eV below and 0.2 eV above silicon mid-gap.…”
Section: Hydrogen Defects Created During Hot Electron Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the chemistry of deuterium and hydrogen is identical deuterium was equally effective in passivating the Si-SiO 2 interface. This development followed a new wave of interests in deuterium for the SiSiO 2 system (19)(20)(21)(22). Integration of deuterium annealing into mainstream semiconductor manufacturing faced some technical challenges (23)(24).…”
Section: Deuterium At Si-sio 2 Interfacementioning
confidence: 99%
“…It is commonly accepted that the interface trap generation is caused by hole and electron injection into the oxide during channel hot carrier stressing or drain avalanche stressing. The recent discovery of the giant deuterium isotope effect in transistor degradation [8]- [11] widely accepted model of interface trap generation by hot carrier injection is true, then carrier injection experiments should exhibit the same giant isotope effect as has been observed for drain avalanche stressing. Such experiments and their consequences for the mechanism of trap generation are the subject of this letter.…”
mentioning
confidence: 99%